Considering CYP1A2 phenotype and genotype for optimizing the dose of olanzapine in the management of schizophrenia. (September 2013) - Perera, Vidya; Gross, Annette S; M Polasek, Thomas; Qin, Yan; Rao, Gauri; Forrest, Alan; Xu, Junzhe; McLachlan, Andrew J
Abstract : Introduction: Schizophrenia, a mental disorder, is a debilitating condition which typically strikes young people in their early 20's. Antipsychotic medications are widely prescribed for the treatment of schizophrenia however a balancing act is necessary to provide the correct dose to each patient. It is suggested that a large number of patients discontinue antipsychotic pharmacotherapy because the treatments provided do not always reduce the positive symptoms of the disease, while many have adverse effects on the patients. This implies that neither the incorrect drug nor the optimal dosage for that patient is achieved. Areas covered: The current review investigates variability in response to olanzapine with a specific focus on the common intrinsic and extrinsic factors that influence both olanzapine and CYP1A2 activity. Furthermore, the authors discuss the utilization of phenotyping and genotyping of CYP1A2 and their potential utility in clinical practice for olanzapine dosing regimens. The authors also consider the potential of pharmacometrics compared to pharmacogenomics as a tool to personalize medicine. Expert opinion: Careful consideration must be given to the impact of a genetic variant on the disposition of a drug prior to implementing genetic 'tests' to determine response. CYP1A2 phenotypic assessment can yield important information regarding the disposition of olanzapine; however, it relies on the accuracy of the metric and the minimal impact of other metabolic pathways. The application of pharmacometrics provides an effective method to establish covariates that significantly influence olanzapine disposition which can incorporate phenotype and/or genotype.